Effects of policy on fertility: A systematic review of (quasi)experiments - Janna Bergsvik; Agnes Fauske; Rannveig K. Hart (Statistics Norway, Research Department, 2020)
This paper describes the results of a systematic review of the literature of policy effects on fertility after 1970 in Europe, USA, Canada and Australia. Empirical studies were selected through extensive systematic searches, with subsequent literature list screening. Inclusion was conditional on implementing an experimental or quasi-experimental design. 57 published papers and recent working papers were included, covering the topics of parental leave, childcare, health services, universal child transfers and welfare reforms. Childcare and universal transfers seem to have the most positive effects on fertility. Few effects were found for parental leave, but this could be linked to these reforms not lending themselves to efficient (quasi)experimental evaluation. Withdrawing cash transfers to families through welfare reforms has limited fertility effects. Subsidizing assisted reproductive technologies show some promise in increasing birth rates of women above age 35.
Keywords: J13; J16; J18; 330; Fertility; Public policy; Family policy; Policy effects; Quasi experiment